Emerging electron microscopy and 3D methodologies to interrogate Staphylococcus aureus osteomyelitis in murine models. Issue 2 (13th January 2021) - de Mesy Bentley, Karen L.; Galloway, Chad A.; Muthukrishnan, Gowrishankar; Echternacht, Scott R.; Masters, Elysia A.; Zeiter, Stephan; Schwarz, Edward M.; Leckenby, Jonathan I.
Abstract: Recent breakthroughs in our understanding of orthopaedic infections have come from advances in transmission electron microscopy (TEM) imaging of murine models of bone infection, most notably Staphylococcus aureus invasion and colonization of osteocyte‐lacuno canalicular networks of live cortical bone during the establishment of chronic osteomyelitis. To further elucidate this microbial pathogenesis and evaluate the mechanism of action of novel interventions, additional advances in TEM imaging are needed. Here we present detailed protocols for fixation, decalcification, and epoxy embedment of bone tissue for standard TEM imaging studies, as well as the application of immunoelectron microscopy to confirm S. aureus occupation within sub‐micron canaliculi. We also describe the first application of the novel Automated‐Tape‐UltraMicrotome system with three‐dimensional reconstruction and volumetric analyses to quantify S. aureus occupation within the osteocyte‐lacuno canalicular networks. Reconstruction of the three‐dimensional volume broadened our perspective of S. aureus colonization of the canalicular network and, surprisingly, revealed adjacent noninfected canaliculi. This observation has led us to hypothesize that viable osteocytes of the osteocyte‐lacuno canalicular networks respond and resist infection, opening future research directions to explain the paradox of adjacent uninfected canaliculi and life‐long deep bone infection in patients with chronic osteomyelitis.